Pithecellobium clypearia: Amelioration Effect on Imiquimod-Induced Psoriasis in Mice Based on a Tissue Metabonomic Analysis - Li, Ying; Zong, Jiaxin; Ye, Wenjun; Fu, Yuanfeng; Gu, Xinyi; Pan, Weisong; Yang, Li; Zhang, Ting; Zhou, Mingmei (Frontiers in Pharmacology, 2021)
Pithecellobium clypearia Benth. (P. clypearia), a popular traditional Chinese medicine, has a significant anti-inflammatory efficacy. The crude water extract of the aerial part of P. clypearia has been clinically applied to treat upper respiratory tract infections, acute gastroenteritis, laryngitis and pharyngitis. However, the therapeutic mechanism of ethanol fraction of water extract (ESW) of P. clypearia to treat psoriasis should be complemented. The aim of our research was to clarify the protective effects of ESW from P. clypearia against psoriasis-like skin inflammation induced by imiquimod (IMQ) in mice with efficacy indexes and target tissue (spleen and serum) metabolomics. The ingredient of ESW was analysed by ultra-high performance liquid chromatography combined with tandem mass spectrometry (UHPLC-MS/MS) method. The imiquimod-induced psoriatic mouse model was employed to investigate the effect of ESW against psoriasis, where treatment method was implemented for 6 days both topically (Gel at 5%) and orally (at 2.4 g/kg p.o.). Traditional pharmacodynamic indicators (phenotypic characteristics, PASI score, H&E staining, immunohistochemical staining, the thickness of epidermis, body weight change, spleen index) were conducted to appraise the efficacy of ESW. Furthermore, a gas chromatography- mass spectrometer (GC- MS) coupled with multivariate analysis were integrated and applied to obtain serum and spleen metabolic profiles for clarifying metabolic regulatory mechanisms of ESW. The current study illustrated that the compose of ESW were mainly gallic acid, ethyl gallate, quercitin, 7-O-galloyltricetiflavan, quercetin, and myricetin by UHPLC-MS/MS analysis. ESW could distinctly improve IMQ-induced psoriasis in mouse through reducing PASI score, alleviating tissue damage, restoring spleen index and inhibiting PCNA expression in psoriasis-like skin tissue. From the metabolomics study, 23 markers with significant changes involved in 8 main pathways in spleen and serum samples, including linoleic acid metabolism, glycine, serine and threonine metabolism, and so on. The current study showed that ESW had obvious anti-psoriasis effects on IMQ-induced psoriasis in mice, which might be attributed to regulating the dysfunction of differential biomarkers and related pathways. In summary, ESW of P. clypearia showed a favourable therapeutic effect on IMQ-induced psoriasis, and metabolomics provided insights into the mechanisms of ESW to the treatment of psoriasis.